Father involvement in family dynamics: a qualitative exploration of perceptions and cultural influences - Gebresilase, Bereket Merkine; Wang, Meiping; Chuanxia, Zhang; Taddese, Esayas Teshome; Elka, Zebdewos Zekarias; Biramo, Yohannes Bisa (Frontiers in Psychology, 2025)
Globally, the role of fathers has expanded beyond financial provision to encompass emotional support, shared household responsibilities, and active involvement in children’s development. Yet in Ethiopia, entrenched patriarchal norms continue to define fatherhood narrowly, positioning men primarily as providers and overseers while relegating care-giving and domestic duties to women. This study explored Ethiopian fathers’ perceptions of their paternal roles and the cultural factors shaping these views. Using a phenomenological qualitative design, semi-structured interviews were conducted with 30 purposively selected fathers from southern Ethiopia, and the data were thematically analyzed with NVivo 12. Findings revealed that most fathers identified their contributions as financial support, social participation, and supervisory roles over maternal care-giving, while emotional nurturing and direct child-rearing were widely regarded as women’s responsibilities. Participation in household tasks such as cooking and childcare was largely limited, reflecting deeply embedded gender norms. These insights highlight the persistence of traditional constructions of fatherhood that constrain male engagement in care-giving, perpetuate gender inequalities, and place disproportionate burdens on mothers. Culturally grounded strategies and policy interventions are therefore needed to re-frame paternal roles, support equitable parenting, and align family practices with international health and development agendas.